PCSK9 deficiency alters brain lipid composition without affecting brain development and function - Pärn, Angela; Olsen, Ditte; Tuvikene, Jürgen; Kaas, Mathias; Borisova, Ekaterina; Bilgin, Mesut; Elhauge, Mie; Vilstrup, Joachim; Madsen, Peder; Ambrozkiewicz, Mateusz C.; Goz, Roman U.; Timmusk, Tõnis; et al. (Frontiers in Molecular Neuroscience, 2023)
PCSK9 induces lysosomal degradation of the low-density lipoprotein (LDL) receptor (LDLR) in the liver, hereby preventing removal of LDL cholesterol from the circulation. Accordingly, PCSK9 inhibitory antibodies and siRNA potently reduce LDL cholesterol to unprecedented low levels and are approved for treatment of hypercholesterolemia. In addition, PCSK9 inactivation alters the levels of several other circulating lipid classes and species. Brain function is critically influenced by cholesterol and lipid composition. However, it remains unclear how the brain is affected long-term by the reduction in circulating lipids as achieved with potent lipid lowering therapeutics such as PCSK9 inhibitors. Furthermore, it is unknown if locally expressed PCSK9 affects neuronal circuits through regulation of receptor levels. We have studied the effect of lifelong low peripheral cholesterol levels on brain lipid composition and behavior in adult PCSK9 KO mice. In addition, we studied the effect of PCSK9 on neurons in culture and in vivo in the developing cerebral cortex. We found that PCSK9 reduced LDLR and neurite complexity in cultured neurons, but neither PCSK9 KO nor overexpression affected cortical development in vivo. Interestingly, PCSK9 deficiency resulted in changes of several lipid classes in the adult cortex and cerebellum. Despite the observed changes, PCSK9 KO mice had unchanged behavior compared to WT controls. In conclusion, our findings demonstrate that altered PCSK9 levels do not compromise brain development or function in mice and are in line with clinical trials showing that PCSK9 inhibitors have no adverse effects on cognitive function.